2013
DOI: 10.1095/biolreprod.113.112177
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Changes in the Porcine Endometrium During the Preattachment Phase1

Abstract: The porcine conceptus undergoes rapid differentiation and expansion of its trophoblastic membranes between Days 11 and 12 of gestation. Concomitant with trophoblast elongation, production of conceptus estrogen, the porcine embryonic pregnancy recognition signal, increases. Conceptus attachment to the uterine surface epithelium starts after Day 13, initiating epitheliochorial placentation. To analyze the transcriptome changes in the endometrium in the course of maternal recognition of pregnancy, deep sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 71 publications
10
74
0
1
Order By: Relevance
“…5 ). Changes in endometrial transcriptome during early stages of conceptus attachment to uterine LE are just beginning to widen our understanding of the critical factors involved with establishment and maintenance of pregnancy in the pig (Samborski et al 2013 ;Chen et al 2015 ;Kiewisz et al 2014 ). The emergence of microRNAs as posttranscriptional players in regulating gene function has added a new area of investigation to enhance understanding of conceptus-endometrial interactions (Krawczynski et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Changes in endometrial transcriptome during early stages of conceptus attachment to uterine LE are just beginning to widen our understanding of the critical factors involved with establishment and maintenance of pregnancy in the pig (Samborski et al 2013 ;Chen et al 2015 ;Kiewisz et al 2014 ). The emergence of microRNAs as posttranscriptional players in regulating gene function has added a new area of investigation to enhance understanding of conceptus-endometrial interactions (Krawczynski et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of the uterine transcriptome during the preimplantation phase has been intensively studied in several species (sheep (73), bovine (74,75), horse (21,76), and pig (77)(78)(79)) and the proteome of uterine fluid during the early stages of pregnancy was analyzed in cattle and sheep (80 -82). Several proteins we found more abundant in the uterine luminal fluid during the luteal phase were also described as uterine markers of early pregnancy with an increased production in the presence of an embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the OPN gene corresponds to the location with the QTL regions for reproductive traits, such as ovulation rate (Rathje et al, 1997), uterine capacity (Rohrer et al, 1999), age of puberty (Cassady et al, 2001), litter size and embryosurvival rate (King et al, 2003), on SSC8 in pigs. Moreover, the function genomic analysis showed that the differential expression levels of the OPN gene were found in the ovarian follicles, ovaries, myometrium and endometrium (Caetano et al, 2004;Fernandez-Roddriguez et al, 2011;Sun et al, 2011;Wang et al, 2013;Samborski et al, 2013). Therefore the OPN gene can be regarded as a candidate gene for the determination of reproductive traits in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have been discovered. One of these genes is osteopontin (OPN) which can be differentially expressed in various reproductive tissues, e.g., ovarian follicles, ovaries, myometrium and endometrium (Caetano et al, 2004;Fernandez-Roddriguez et al, 2011;Sun et al, 2011;Wang et al, 2013;Samborski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%